2022
DOI: 10.1186/s12903-022-02441-6
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese version of the Oral Health Impact Profile-14 (OHIP-14) questionnaire among college students: factor structure and measurement invariance across genders

Abstract: Background The Oral Health-related Quality of Life (OHRQoL) is a multi-dimensional concept commonly used to examine the impact of health status on quality of life, and the Oral Health Impact Profile-14 (OHIP-14) questionnaire is a good self-assessment tool. This study was designed to investigate the factor structure of the OHIP-14 scale Chinese version, measurement invariance and latent mean differences across genders among college students. Methods The online survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Furthermore, there were significant differences in the scores of OHIP between different gender groups in a survey of patients with dentofacial deformities in Brazil [ 32 ]. Similar results were also seen in the Chinese college student population [ 19 ]. Thus, accumulating surveys showed that sex differences may be a significant factor impacting OHRQoL, and it is possible that the latent variable of gender may have an impact on the score of the Chinese version of OHIP-14 in the assessment of individuals of various genders.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, there were significant differences in the scores of OHIP between different gender groups in a survey of patients with dentofacial deformities in Brazil [ 32 ]. Similar results were also seen in the Chinese college student population [ 19 ]. Thus, accumulating surveys showed that sex differences may be a significant factor impacting OHRQoL, and it is possible that the latent variable of gender may have an impact on the score of the Chinese version of OHIP-14 in the assessment of individuals of various genders.…”
Section: Introductionsupporting
confidence: 87%
“…The CFA results demonstrated that the 7-factor scale of the OHIP-14 has a better fit for the clinical populations. The same results were also found in the Chinese version of OHIP-14 tested on Chinese college students [ 19 ], indicating that the 7-factor structure of the Chinese version of OHIP-14 can be well applied to both clinical and non-clinical populations. According to the G D Slade’s study, OHIP-14 is a simplified version of OHIP-49 with high reliability and contains questions from each of the seven conceptual dimensions of the OHIP-49 [ 10 ].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Dussor et al (2018) proposed that the oral and facial morbidity of men and the elderly is high. In addition, our previous research has also proved that education will also affect OFP, for example, the high incidence of OFP can be observed among college students (Feng et al, 2022). Given the above results, it cannot be ruled out whether the population is affected by latent variables (gender, age, education, etc.)…”
Section: Assessing the Ofpmentioning
confidence: 92%